Analysis of Dairy Farmers Cooperative Partnership and Participation toward Cooperative Performance to Increase Farmer's Income - Dimas Pratidina Puriastuti Hadiani; Muhammad Nur Ihsan; Puguh Surjowardojo; Bambang Ali Nugroho (ANIMAL PRODUCTION, 2022)
The purpose of this study was to analyze the direct and indirect effect of cooperative partnerships,farmer participation and cooperative performance on farmer’s income. This research method was carried outby distributing questionnaires to 164 farmers as research respondents in Kemiri village who were activemembers of the Agroniaga Cooperative Jabung. The research variables were X1 (cooperative partnership), X2(farmers participation), Y1 (cooperative performance), Y2 (farmer's income). The data obtained were analyzedby path analysis using SPSS. The results show that 1) cooperative partnerships have a significant effect directlyon the cooperative performance at 0.533, 2) farmer participation has a significant effect directly on thecooperative performance at 0.362, 3) the cooperative partnership has a significant effect directly on the incomeof farmers at 0.341, 4) farmer participation has a significant effect directly on the income of farmers at 0.426, 5)cooperative performance has a significant effect directly on the income of farmers at 0.180, 6) cooperativepartnership has no significant effect indirectly on the income of farmers through the cooperative performanceat 0.096, 7) farmer participation has no significant effect indirectly on farmer income through cooperativeperformance at 0.18. This study concludes that 1) cooperative partnerships and farmer participation havesignificant effect directly on the cooperative performance, 2) cooperative partnerships, farmer participation,and cooperative performance have a significant effect directly on farmers' incomes, 3) cooperative partnershipsand farmer participation have no significant effect indirectly on farmer income through cooperativeperformance.